2013
DOI: 10.1051/0004-6361/201321421
|View full text |Cite
|
Sign up to set email alerts
|

The distance to the young open cluster Westerlund 2

Abstract: A new X-ray, UBVRI c , and JHKs study of the young cluster Westerlund 2 was undertaken to resolve discrepancies tied to the cluster's distance. Existing spectroscopic observations for bright cluster members and new multi-band photometry imply a reddening relation toward Westerlund 2 described by E U−B /E B−V = 0.63 + 0.02 E B−V . Variable-extinction analyses for Westerlund 2 and nearby IC 2581 based upon spectroscopic distance moduli and ZAMS fitting yield values of R V = A V /E B−V = 3.88±0.18 and 3.77±0.19, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…However, these distances are derived on the asumption of an RV = 3.1 extinction law, yielding an average AV = 4.68 for the cluster. Carraro et al (2012) have claimed an anomalous extinction law along this line of sight with an average RV = 3.8± 0.2. These authors use the spectra of Rauw et al to obtain AV = 7.1± 1.2, corresponding to a much smaller distance of 3.02 ± 0.52 kpc.…”
Section: B02 Westerlundmentioning
confidence: 77%
“…However, these distances are derived on the asumption of an RV = 3.1 extinction law, yielding an average AV = 4.68 for the cluster. Carraro et al (2012) have claimed an anomalous extinction law along this line of sight with an average RV = 3.8± 0.2. These authors use the spectra of Rauw et al to obtain AV = 7.1± 1.2, corresponding to a much smaller distance of 3.02 ± 0.52 kpc.…”
Section: B02 Westerlundmentioning
confidence: 77%
“…There is general agreement in the literature that Wd2 is younger than 3 Myr and that its core might be younger than 2 Myr (Ascenso et al 2007;Carraro et al 2013). In our first paper (Zeidler et al 2015, hereafter Paper I) we confirmed the cluster distance of VargasÁlvarez et al (2013) of 4.16 kpc, using Hubble Space Telescope (HST) photometry and our highresolution 2D extinction map.…”
Section: Introductionmentioning
confidence: 81%
“…That analysis relies on WISE midinfrared data (Wright et al 2010) to determine extinction law variations via the color-extrapolation method. For comparison, certain regions in Carina and the Galactic bulge adhere to an anomalous extinction law (Pietrukowicz et al 2012;Carraro et al 2013).…”
Section: Extinction and Distancementioning
confidence: 99%